CD25+ B-1a Cells Express Aicda - Kaku, Hiroaki; Holodick, Nichol E.; Tumang, Joseph R.; Rothstein, Thomas L. (Frontiers in Immunology, 2017)
Abstract B-1a cells are innate-like B lymphocytes, producing natural antibodies. Activation Induced Cytidine Deaminase (AID), a product of the Aicda gene, plays a central role in class-switch recombination and somatic hypermutation in B cells. Although a role for Aicda in B-1a cells has been suggested on the basis of experiments with knock-out mice, whether B-1a cells express Aicda, and if so, which B-1a cell subpopulation expresses Aicda, remains unknown. Here, we demonstrate that B-1 cells express Aicda, but at a level below that expressed by germinal center B cells. We previously reported that B-1a cells can be subdivided based on CD25 expression. We show here that B-1a cell Aicda expression is concentrated in the CD25+ B-1a cell subpopulation. These results suggest the possibility that previous studies of memory B cells identified on the basis of Aicda expression may have inadvertently included an unknown number of CD25+ B-1a cells. Although B-1a cells develop normally in the absence of Aicda, a competitive reconstitution assay reveals enhanced vigor for AID KO B-1a cell bone marrow (BM) progenitors, as compared with wild type BM B-1 cell progenitors. These results suggest that AID inhibits the development of B-1a cells from BM B-1 cell progenitors in a competitive environment.